TREATMENT OF HYPOTROPHIC HEMS - G. E. Karapetyan; Yu. S. Vinnik; M. I. Gulman; R. A. Pakhomova; L. V. Kochetova; N. M. Markelovа; E. S. Vasilenya; E. V. Dyabkin; N. I. Tsedrik (Креативная хирургия и онкология)
The problem  of treatment of patients with cicatricial defects of a skin concerns one of actual sections  of medicine. The new method of treatment of hypotrophic hems by a beam of the laser from  a long wave of 540  nanometers, duration of impulses 1 - 2 nanoseconds (a mode  of generation Q – sw),  energy  of an impulse  (50  - 150 мДж)  and  frequency of following of an impulse (1-4 Hz) is offered. Its influence on microcirculation of a bottom of a hem that promotes reduction of depth of a hem, improvement of its consistence is proved. At use of a method healing  passes  during  30 – 38 days,  with formation a normotrophic hem, skin color restoration.